Fabrication and characterization of microfluidic field effect transistor on silicon substrate - Maizatul Zolkapli (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2010)
The development of a silicon-based microfluidic field effect transistor has been carried out. The main objective of this study is to present from concept, the design of a microfluidic FET and to develop its appropriate process flow in fabricating the microfluidic FET on silicon wafer, which will finally be characterized using a suitable test methodology. Hence, fabrication on a p- <100> 4 inch silicon wafer by photolithography, wet chemical etching, thermal oxidation, diffusion and metallization with focus on a liquid conduction path has been executed. A three level photo mask has been designed via AutoCAD and chrome printed on soda-lime glass. The basic structure of the device is adapted from the conventional MOSFET structure and redesigned to incorporate a liquid channel in its operation. Therefore, the functionality remains unchanged but the principal conduction path is replaced by a fluid instead of a doped semiconductor. Two reservoirs are connected via a channel with source and drain regions doped on opposite sides of the liquid channel to reduce conduction through the substrate.